Deciphering the aetiology of a mixed fungal infection by broad‐range PCR with sequencing and fluorescence in situ hybridisation. Issue 6 (8th April 2013) - Rickerts, V.; McCormick Smith, I.; Mousset, S.; Kommedal, O.; Fredricks, D. N.
Summary: Simultaneous infections with multiple fungi may be misinterpreted as monomicrobial infections by current diagnostics with ramifications for the choice of antimicrobial agents that may impact patient outcomes. The application of molecular methods on tissue samples may be useful to decipher the aetiology of mixed fungal infections. We present a leukaemic patient who died from sepsis due to candidaemia. The postmortem examination documented fungal elements in lung tissue. Fungal DNA was amplified from the lung sample by broad‐range PCR assays targeting the 28S ribosomal RNA gene or the internal transcribed spacer 2 (ITS‐2). Fluorescence in situ hybridisation (FISH) using differentially labelled fungal probes was applied on the tissue. Sequencing identified the PCR amplicons as Aspergillus fumigatus (28S assay) and Candida tropicalis (ITS‐2 assay). As a chromatogram suggested mixed amplicons, the Isentio ripseq ® tool for in silico analysis was applied and confirmed the presence of both amplicons in the PCR products of both assays. FISH confirmed the presence of Aspergillus and Candida within the infectious process, a prerequisite for inferring a causal relationship with the infection. The combination of broad‐range PCR with sequence analysis and FISH applied on tissue samples is a powerful approach to identify the aetiology of invasive fungal infections, including mixed infections.